The Use of Micro capsulated Feed as Alternative to Artemia sp. in The Food of Guppy and Goldfish Larvae - Mahmut Yanar; Çiğdem Çalım Akray; Ece Evliyaoğlu; Zeynep Erçen (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the effects of Artemia sp. nauplii and micro capsulated feed on growth performance and survival rate of guppy (Poecilia reticulata) and goldfish (Carassius auratus) larvae were compared at the end of three weeks of rearing period. Length of goldfish larvae (4.82 mm) fed Artemia sp. (from 4 to 12/mL/day) were between 7.97 and 9.76 mm at the end of the trial while these values were between 6.80 and 7.21 mm for those fed microencapsulated feed (from 10 to 30 mg/L/day). On the other hand length of guppy larvae fed Artemia sp. (from 5 to 25/mL/day) were between 13.02 and 17.00 mm, whereas these values were remained between 11.98 and 12.38 mm for those fed microencapsulated feed (from 10 to 40 mg/L/day). A similar result was also observed in survival rates. Survival rate of goldfish larvae fed Artemia sp. were 88.91-97.61% in while those fed microencapsulated feed were 6.19-87.14%. On the other hand survival rate of guppy larvae fed Artemia sp. were 99.17-100.00% whereas those fed microencapsulated feed were 57.50-87.50%. Eventually, microencapsulated feed was not as successful as Artemia sp. on the growth and survival rate of larvae of both species.